Bats in the Ghats: Agricultural intensification reduces functional diversity and increases trait filtering in a biodiversity hotspot in India. (June 2017) - Wordley, Claire F.R.; Sankaran, Mahesh; Mudappa, Divya; Altringham, John D.
Abstract: The responses of bats to land-use change have been extensively studied in temperate zones and the neotropics, but little is known from the palaeotropics. Effective conservation in heavily-populated palaeotropical hotspots requires a better understanding of which bats can and cannot survive in human-modified landscapes. We used catching and acoustic transects to examine bat assemblages in the Western Ghats of India, and identify the species most sensitive to agricultural change. We quantified functional diversity and trait filtering of assemblages in forest fragments, tea and coffee plantations, and along rivers in tea plantations with and without forested corridors, compared to protected forests. Functional diversity in forest fragments and shade-grown coffee was similar to that in protected forests, but was far lower in tea plantations. Trait filtering was also strongest in tea plantations. Forested river corridors in tea plantations mitigated much of the loss of functional diversity and the trait filtering seen on rivers in tea plantations without forested corridors. The bats most vulnerable to intensive agriculture were frugivorous, large, had short broad wings, or made constant frequency echolocation calls. The last three features are characteristic of forest animal-eating species that typically take large prey, often by gleaning. Ongoing conservation work to restore forest fragments and retain native trees in coffee plantations should be highly beneficial for bats in this landscape. The maintenance of a mosaic landscape with sufficient patches of forest, shade-grown coffee and riparian corridors will help to maintain landscape wide functional diversity in an area dominated by tea plantations. Graphical abstract: Highlights: Bat functional diversity was similar in shade coffee to protected forests. Bat functional diversity was similar in forest fragments to protected forests. Tea plantations retain far less bat functional diversity than shade grown coffee. Large bats and bats with short, broad wings were filtered out in modified habitats. Riparian corridors help retain bat functional diversity in a modified landscape.